Energy-economic-environmental analysis of solar drying system: a review - Wan Nurlaila Yusra Mat Desa; Ahmad Fudholi; Zahira Yaakob (International Journal of Power Electronics and Drive Systems (IJPEDS), 2020)
Solar drying is an emerging technology to preserve wide range of products from agriculture to animal-based products. The application of solar dryers, however must be evaluated to determine its benefit and effectiveness. In the evaluation of solar dryer performance, three criteria which are most important to look at are thermal performance, economic cost and environmental implications. Therefore, this paper attempts to review the thermoeconomic analysis and environmental evaluation on various solar drying system. Performance equations in energy–economic–environment analyses for solar drying syistems evaluation are presented. The CO2 emission, carbon mitigation, and earned carbon credit of various solar drying syistem are also presented.